The Effect Phineas Taylor Barnum’s Ambition In Jenny Bicks’ The Greatest Showman - Siti Faizureah; Cahyaningsih Pujimahanani (PT. Padang Tekno Corp, 2025)
This article focuses on the analysis of Phineas Taylor Barnum’s ambition in Jenny Bicks’ The Greatest Showman. The study aims to explain how Barnum’s ambition affects his character development. The research uses a qualitative descriptive method with individual psychology as the framework, combining intrinsic and extrinsic approaches with both deductive and inductive techniques. The data come from Barnum’s dialogues and actions in the script, collected through close reading. The Greatest Showman tells the story of Barnum, a man with great ambition who rises from poverty to become a famous showman, but also struggles with family, recognition, and self-discovery. The findings show that Barnum’s ambition has two main effects: personal growth, reflected in his confidence, resilience, and family awareness; and personal development, reflected in his leadership, creativity, and decision-making. The study concludes that ambition, when directed positively, becomes a driving force that shapes Barnum’s character transformation.